2017
DOI: 10.1002/jmri.25921
|View full text |Cite
|
Sign up to set email alerts
|

DCE‐MRI texture analysis with tumor subregion partitioning for predicting Ki‐67 status of estrogen receptor‐positive breast cancers

Abstract: 4 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 41 publications
4
68
0
1
Order By: Relevance
“…For example, the feature of difference entropy, which measures heterogeneous textural appearance, i.e., randomness of the difference in neighboring voxel gray levels, was high in low Ki-67 expression tumors [49]. Moreover, a related study found that luminal A tumors had a higher value of this feature than luminal B tumors did [20]. Our results are partly consistent with those of the previous study because the Ki-67 index has also been used as a proliferation marker to distinguish between the luminal A and luminal B molecular subtypes of ER-positive breast cancer [50].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the feature of difference entropy, which measures heterogeneous textural appearance, i.e., randomness of the difference in neighboring voxel gray levels, was high in low Ki-67 expression tumors [49]. Moreover, a related study found that luminal A tumors had a higher value of this feature than luminal B tumors did [20]. Our results are partly consistent with those of the previous study because the Ki-67 index has also been used as a proliferation marker to distinguish between the luminal A and luminal B molecular subtypes of ER-positive breast cancer [50].…”
Section: Discussionmentioning
confidence: 98%
“…However, to predict tumor characteristics, only a single parametric MRI is usually used. For example, studies indicate that radiomic analysis of MRI may be helpful in predicting breast cancer subtypes [13][14][15][16], neoadjuvant chemotherapy responses [17][18][19], Ki-67 expression level [20][21][22], pathological stage [23], histological grade [24], tumor malignancy [25,26], and breast cancer risk [27] based on either DCE-MRI or DWI. These studies were performed without considering complementary information that could be provided by different parametric images.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinds of quantitative methods have been applied to the differentiation of benign from malignant breast lesions based on DCE‐MRI 28‐32 . However, most previous studies showed that heterogeneity investigations based on post‐contrast images were commonly separate from analyses based on kinetic parametric maps 33‐35 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, quantifying the spatial heterogeneity in vascularization of the whole tumor volume from DCE‐MRI data may be more informative and realistic. In that sense, radiomics approaches on DCE‐MRI have recently shown encouraging results, alone or with other MRI sequences, in order to improve the detection of prostate cancer, to distinguish benign and malignant adnexal masses, to identify relevant molecular subtypes of breast cancers, to detect lymph node metastases in breast cancers, or to predict response to neoadjuvant treatment for rectum, breast, and nasopharyngeal cancers . Soft‐tissue sarcomas (STS) are malignant mesenchymal tumors with important inter‐ and intratumoral heterogeneity known to be associated with high grade .…”
mentioning
confidence: 99%
“…In that sense, radiomics approaches on DCE-MRI have recently shown encouraging results, alone or with other MRI sequences, in order to improve the detection of prostate cancer, to distinguish benign and malignant adnexal masses, to identify relevant molecular subtypes of breast cancers, to detect lymph node metastases in breast cancers, or to predict response to neoadjuvant treatment for rectum, breast, and nasopharyngeal cancers. [5][6][7][8][9][10][11][12] Soft-tissue sarcomas (STS) are malignant mesenchymal tumors with important inter-and intratumoral heterogeneity known to be associated with high grade. 13 Previous studies have shown that DCE-MRI could be useful to predict response to chemotherapy in high-grade STS, [14][15][16][17] as well as radiomics approaches.…”
mentioning
confidence: 99%